Pengaruh Pemberian Senam Hamil Terhadap Tingkat Kecemasan Dan Kualitas Tidur Ibu Hamil di Klinik Pratama Salbiyana Kecamatan Deli Serdang Tahun 2023 - Suci Rezeki Syahputri Sitepu; Vitalia Hanako Murni Simanjuntak; Markus Doddy Simanjuntak; Sonia Novita Sari; Mediana Sembiring (Student Research Journal, 2023)
Indonesia's exclusive breastfeeding coverage is still far from the national target of 80%. The results of the 2013 Indonesian Health Demographic Survey (SDKI) showed that coverage of exclusive breastfeeding for babies 0-6 months was only 42%. This research used a praexperiment (an experimental activity that aims to determine the effect that arises as a result of certain treatment) using a one group pretest-posttest design, to see the effect of oxytocin massage on the smooth flow of breast milk at the Roslena Clinic Medan Johor. The conclusion is that there is an effect of Oxytocin Massage on the smooth flow of breast milk at the Roslena Clinic Medan Johor. It is hoped that Roslena Clinic Medan Johor will increase the implementation of oxytocin massage to prevent babies from not sleeping peacefully for 3-4 hours due to irregular milk production in breastfeeding mothers.